Free convection flow in vertical cylinder with heat sources of power law fluid - Quang, Vu Duy; Que, Nguyen Van (Vietnam Journal of Mechanics, 1996)
In this paper the free convection flow of power law fluid in cylindrical channel with heat sources is investigated. The heat sources are in the fluid as well as inside the channel wall and are assumed constant and uniform distributed. The problem is solved by finite difference method. An asymptotic solution is given. The results with heat sources and without ones are compared.